Modelling ultraviolet threats - James, Itor (SPIE, 2016)
Electro-optically (EO) guided surface to air missiles (SAM) have developed to use Ultraviolet (UV) wavebands supplementary to the more common Infrared (IR) wavebands. Missiles such as the US Stinger have been around for some time but are not considered a proliferation risk. The Chinese FN-16 and Russian SA-29 (Verba) are considered a much higher proliferation risk. As a result, models of the missile seekers must be developed to understand the characteristics of the seeker and the potential performance enhancement that are included. Therefore, the purpose of this paper is to introduce the steps that have been taken to characterise and model these missiles. It begins by outlining some of the characteristics of the threats, the key elements of a UV scene, the potential choice of waveband for a detector, the initial modelling work to represent the UV detector of the missile and presents initial results. The modelling shows that the UV detection range of a typical aircraft is dependent on both the size of the aircraft and its reflectivity. However, the strength of this correlation is less than expected. As a result, further work is required to model more seeker types and to investigate what is causing the weak correlations found in these initial investigations. In addition, there needs to be further study of the sensitivities of the model to other variables, such as the modelled detectivity of the detector and the signal to noise ratio assumed. Overall, the outcome of this work will be to provide specifications for aircraft size and reflectivity that limit the effectiveness of the UV channels.
Keywords: Missiles; Ultraviolet